1985
DOI: 10.1007/bf01403839
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal inflammation in patients with nonulcer dyspepsia

Abstract: Proper control and quantitation are important in the accurate evaluation of gastroduodenal inflammation in dyspeptic patients without ulcers or erosions as proved by endoscopy. The endoscopic findings and the gastroduodenal mucosal inflammatory cell count in 31 patients with non-ulcer dyspepsia were compared with an age-matched group of 32 healthy controls. Endoscopy revealed similar mucosal changes and in similar frequency in both groups. Differential mucosal inflammatory cell count showed a statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 36 publications
4
29
0
Order By: Relevance
“…Furthermore, when the histological atrophic grade was compared between the group with atrophy absent by endoscopy and the group with atrophy present the histological atrophic grade was significantly higher in the group with atrophy present by endoscopy than in the group with atrophy absent. These results are consistent with the findings that the concordance was good in the severe forms of gastritis [11][12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Furthermore, when the histological atrophic grade was compared between the group with atrophy absent by endoscopy and the group with atrophy present the histological atrophic grade was significantly higher in the group with atrophy present by endoscopy than in the group with atrophy absent. These results are consistent with the findings that the concordance was good in the severe forms of gastritis [11][12][13][14][15][16][17].…”
Section: Discussionsupporting
confidence: 95%
“…Research regarding the concordance between the findings of endoscopy and histology in cases with gastritis has been made, but the outcomes showed a kind of disappointing correlation [11][12][13][14][15]. However, in general, the concordance was good in the severe forms of gastritis and normal endoscopy has excluded active gastritis [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of C. pylori in patients with NUD is 45 to 70% and the prevalence of gastritis is similar (68,77,109,110,126,127), suggesting possible involvement of the organism in the disease. One of the problems with assessing these data is that there is an age-related increase in the prevalence of the organism (43,50,92), and, thus, C. pylori is found in about 50% of asymptomatic individuals 50 to 60 years old.…”
Section: Nudmentioning
confidence: 87%
“…Though this variety of gastritis has been well defined morphologically [42], both its pathophysiology and relationship to clinical symptoms remain uncertain [13. [43][44][45][46][47], Thus, some consider that the primary problem in antral gastritis is abnormal duodenogastric bile reflux, consequent on abnor malities of gastropyloroduodenal coordina tion [10,48], Support for this concept of bilerelated gastritis comes from in vitro studies which have clearly demonstrated the ability of bile both to disrupt the mucus layer [49] and to inhibit gastric bicarbonate secretion [50], thus allowing easy access for damaging hydrogen ions to the sensitive mucosa. Our observations suggest furthermore that the at tack-defense equilibrium in the antrum may already be set on a knife edge, the additional presence of bile in certain pathological condi tions tilting the balance and resulting in mu cosal damage.…”
Section: Discussionmentioning
confidence: 99%